Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Find all the zeros of the equation.
-x^3-x^2=11x+11


Sagot :

Answer:

x= -1 , i(sqrt11) , -i(sqrt11)

Step-by-step explanation:

subtract 11x from both sides

-x^3 - x^2 - 11x = 11

subtract 11 from both sides

-x^3 - x^2 - 11x - 11 = 0

Factor the left side of the equation

- (x - 1)(x^2 + 11) = 0

Set both factors to zero and solve for x

x + 1 = 0 x^2 + 11 = 0

-1 -11

x^2 = -11

x = -1 x = +/- i(sqrt11)